Spectroscopic structure of two interacting electrons in a quantum dot by the shifted expansion method - Elsaid, Mohammad K. (My University, 2000)
The shifted (Formula presented) expansion method has been used to study the relative Hamiltonian of two interacting electrons confined in a quantum dot. The eigenenergy spectra are obtained for any arbitrary ratio of Coulomb to confinement energies. Interesting features of the quantum dot spectra, such as the energy-level crossings and the removal of the degeneracy, are explained. Comparisons show that our results are in very good agreement with recent published ones calculated by exact and WKB methods. © 2000 The American Physical Society.